Method for solving nickel loss in sintering of solid oxide fuel cell

By printing NiO slurry on the fuel electrode surface of the solid oxide fuel cell and co-sintered, the nickel loss problem caused by contact between the nickel oxide and the scorching plate is solved, the proportional consistency of the fuel electrode is maintained, and the performance and stability of the battery are improved.

CN119890377APending Publication Date: 2025-04-25CHANGZHOU YIJING HYDROGEN ENERGY TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411915010.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

During the sintering process of solid oxide fuel cells, nickel oxide (NiO) contacts with the scorched plate, causing nickel loss, resulting in imbalance in the fuel electrode surface ratio, affecting the battery's conductivity and catalytic performance.

Method used

NiO slurry is printed on the fuel electrode surface, and after drying, it is co-sintered with the electrolyte layer or barrier layer to ensure that the ratio of NiO and YSZ is consistent and to prevent nickel loss.

Benefits of technology

It effectively solves the problem of nickel loss, maintains the conductivity and catalytic performance of the fuel electrode, improves the overall battery performance, and provides convenience for the production of industrial stacks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005206630060000011
    Figure HDA0005206630060000011
  • Figure HDA0005206630060000012
    Figure HDA0005206630060000012
  • Figure HDA0005206630060000021
    Figure HDA0005206630060000021
Patent Text Reader

Abstract

The invention relates to the technical field of solid oxide, in particular to a method for solving nickel loss in sintering of a solid oxide fuel cell, which at least comprises the following steps: (1) preparing NiO slurry; (2) for the solid oxide fuel cell supported by the fuel electrode, before the step of co-sintering the fuel electrode and the electrolyte layer, printing NiO slurry on the surface of the fuel electrode, and after drying, co-sintering the fuel electrode and the electrolyte layer; for the solid oxide fuel cell supported by the electrolyte, before the fuel electrode sintering step, the NiO slurry is printed on the surface of the fuel electrode, and the fuel electrode and the fuel electrode are co-sintered after drying, so that the method is simple, convenient and economical, the performance of the cell can be further improved, and large-scale industrial popularization and implementation are easy to realize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid oxides, in particular to a method for solving the problem of nickel loss during sintering of solid oxide fuel cells. Background Art

[0002] Reversible solid oxide fuel cell (RSOC) is an all-solid-state electrochemical energy conversion device that integrates solid oxide fuel cell (SOFC) and solid oxide electrolyzer (SOEC). It can efficiently convert chemical energy and electrical energy in fuel, and has great commercial value and broad application prospects. According to the shape of the battery, RSOC can be divided into tubular and flat types; tubular batteries are easy to seal when assembled into a battery stack, and flat type has a higher energy density. Currently, RSOC used in industrial power generation and hydrogen production is mainly flat type. Flat-plate reversible solid oxide fuel cells are divided into electrolyte-supported and fuel-electrode-supported types; fuel-electrode-supported ones have a higher power density due to their thinner electrolyte and shorter current transmission path, and are widely used in high-temperature fuel cell power generation projects. Electrolyte-supported batteries have a large ohmic resistance and generate a large amount of heat under high current density operating conditions, making them more suitable for hydrogen production before the thermoneutral voltage. In addition, due to the thinner fuel electrode, their long-term stability is also better than that of fuel-electrode-supported batteries. Therefore, electrolyte-supported batteries are widely used in high-temperature water electrolysis hydrogen production projects.

[0003] Whether it is a fuel-electrode-supported or electrolyte-supported solid oxide fuel cell, the preparation process cannot be separated from the high-temperature sintering process. Fuel-electrode-supported solid oxide cells usually use a co-sintering process to co-sinter an electrolyte layer less than 10μm thick with an anode support layer of about 500μm thick. Due to the inconsistency of the composition and porosity of the electrolyte layer material and the anode material, there will be a difference in thermal expansion coefficient, which will cause inconsistent shrinkage during the sintering process. Usually, in order to ensure the density of the electrolyte layer, the fuel-electrode-supported cell will bend toward the anode; at the same time, in order to ensure the flatness of the battery and facilitate integration, fuel-electrode-supported cells often add a pressure plate during the sintering process to limit the bending of the battery. At this time, the NiO with a thickness of about 1-3μm at the bottom of the fuel electrode will react significantly with the alumina support plate at high temperature. Even if a zirconium oxide support plate is used, NiO will migrate from the surface of the fuel electrode to the surface of the support plate, causing NiO loss. Since the fuel electrode is a mixed material of NiO and YSZ, the loss of NiO will cause an imbalance in the surface ratio of the fuel electrode, affecting the conductivity and catalytic performance of the battery, thereby affecting the performance of the entire battery. Electrolyte-supported batteries usually sinter the electrolyte layer first, and then print the barrier layer and fuel electrode on both sides of the electrolyte through a screen printing process, and then co-fire the barrier layer and fuel electrode at high temperature. The fuel electrode is often close to the support plate, and there will also be NiO loss. Since the fuel electrode is often less than 20μm, the loss of NiO will have a much greater impact on the performance of electrolyte-supported batteries than on fuel-supported batteries. The Chinese patent (authorization announcement number is CN202111610611) proposes using nickel-based porous ceramic plates to support battery firing, but the price of nickel-based porous ceramic plates is relatively high, not as good as commonly used alumina or zirconia ceramic plates.

[0004] Therefore, it is very important to solve the NiO loss problem in the sintering process of existing solid oxide fuel cells on alumina or zirconia support plates. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a method for solving the nickel loss during the sintering of solid oxide fuel cells. The method is simple, economical and can further improve the performance of the battery, and is easy to implement on a large scale industrial scale.

[0006] In one aspect, the present invention provides a method for solving the problem of nickel loss during sintering of solid oxide fuel cells, comprising at least the following steps:

[0007] (1) Preparing NiO slurry;

[0008] (2) For solid oxide fuel cells supported by the fuel electrode, NiO slurry is printed on the surface of the fuel electrode before the co-sintering step of the fuel electrode and the electrolyte layer, and the fuel electrode and the electrolyte layer are co-sintered after drying; For solid oxide fuel cells supported by the electrolyte, NiO slurry is printed on the surface of the fuel electrode before the sintering step of the fuel electrode, and the co-sintering with the fuel electrode is carried out after drying.

[0009] As a preferred technical solution, the fuel-electrode-supported solid oxide fuel cell is formed by a molding method selected from tape casting, extrusion molding, injection molding, tableting molding, and phase conversion molding.

[0010] As a preferred technical solution, the electrolyte in the electrolyte-supported solid oxide fuel cell is selected from one of 8YSZ, ScSZ, CeScSZ, and YScSZ.

[0011] As a preferred technical solution, the thickness of the NiO slurry printed on the fuel electrode surface is less than 5 μm.

[0012] As a preferred technical solution, the raw materials for preparing the NiO slurry include at least 30-90% NiO powder, 1-6% dispersant, and the balance made up by organic carrier, calculated by mass percentage.

[0013] As a preferred technical solution, the D of the NiO powder 50 The particle size range is: 0.5-3μm, preferably 1μm.

[0014] As a preferred technical solution, the organic carrier at least includes terpineol and ethyl cellulose.

[0015] Preferably, the organic carrier further comprises 3-hydroxy-2,2,4-trimethylpentyl isobutyrate.

[0016] Preferably, the mass ratio of terpineol, 3-hydroxy-2,2,4-trimethylpentyl isobutyrate and ethyl cellulose is (5-9):(1-3):(0.1-1), preferably 7.8:1.8:0.4.

[0017] As a preferred technical solution, the preparation method of the organic carrier is: ethyl cellulose is mixed with pinene alcohol and 3-hydroxy-2,2,4-trimethylpentyl isobutyrate, and then placed at 100-120° C. for 4-5 hours to obtain the organic carrier.

[0018] As a preferred technical solution, the preparation method of the NiO slurry is: NiO powder, dispersant and organic carrier are stirred and mixed, and then rolled until the slurry fineness is less than 3 μm to obtain NiO slurry.

[0019] As a preferred technical solution, the dispersant at least includes phosphate ester.

[0020] The present invention designs a NiO slurry printing step in the solid oxide fuel cell preparation process, especially optimizes the NiO slurry formula system and controls the thickness of the NiO slurry printed on the fuel electrode surface to be less than 5μm, effectively solving the problem that the solid oxide fuel cell fuel electrode contacts the sintering plate during the sintering process, causing NiO loss, resulting in an imbalance in the ratio of NiO and YSZ, a decrease in battery conductivity, a weakening of catalytic ability, and ultimately affecting the overall performance of the battery. Furthermore, the present invention reduces the NiO slurry printing step in the solid oxide fuel cell preparation process, especially optimizes the NiO slurry formula system and controls the thickness of the NiO slurry printed on the fuel electrode surface to be less than 5μm, effectively solving the problem that the solid oxide fuel cell fuel electrode contacts the sintering plate during the sintering process, causing NiO loss, a imbalance in the ratio of NiO and YSZ, a decrease in battery conductivity, a weakening of catalytic ability, and ultimately affecting the overall performance of the battery. 50 NiO powder with a particle size range of 0.5-3μm is dispersed in an organic carrier system composed of pinene alcohol, 3-hydroxy-2,2,4-trimethylpentyl isobutyrate and ethyl cellulose under the action of phosphate ester. This not only ensures that the ratio of NiO and YSZ in the fuel electrode remains consistent before and after sintering, solving the problem of NiO loss in the fuel electrode, but also sinters a thin current collecting layer at the fuel electrode, thereby improving the performance of the battery and providing convenience for the production of industrial fuel cells.

[0021] Beneficial Effects

[0022] 1. The present invention provides a method for solving the problem of nickel loss during the sintering of solid oxide fuel cells. The method is simple, economical and can further improve the performance of the battery, and is easy to implement on a large scale for industrial promotion.

[0023] 2. The present invention designs a NiO slurry printing step during the preparation process of solid oxide fuel cells, especially optimizes the NiO slurry formula system and controls the thickness of the NiO slurry printed on the fuel electrode surface to be less than 5μm, thereby effectively solving the problem that during the sintering process of the solid oxide fuel cell fuel electrode, the contact between the fuel electrode and the support plate causes NiO loss, resulting in an imbalance in the ratio of NiO and YSZ, a decrease in battery conductivity, a weakening of catalytic ability, and ultimately affecting the overall performance of the battery.

[0024] 3. The present invention adopts D 50 NiO powder with a particle size range of 0.5-3μm is dispersed in an organic carrier system composed of pinene alcohol, 3-hydroxy-2,2,4-trimethylpentyl isobutyrate and ethyl cellulose under the action of phosphate ester. This not only ensures that the ratio of NiO and YSZ in the fuel electrode remains consistent before and after sintering, solving the problem of NiO loss in the fuel electrode, but also sinters a thin current collecting layer at the fuel electrode, thereby improving the performance of the battery and providing convenience for the production of industrial fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1A comparison chart of discharge test data of solid oxide fuel cells supported by two 100*100*0.40 mm industrial-grade fuel electrodes provided in Example 1 and Comparative Example 1, wherein the solid line in the figure is Example 1 and the dotted line is Comparative Example 1.

[0026] Figure 2 A comparison chart of test data for hydrogen production from water by electrolysis of two 100*100*0.25 mm industrial-grade electrolyte-supported solid oxide fuel cells provided for Example 2 and Comparative Example 2, wherein the solid line in the figure represents Example 2 and the dotted line represents Comparative Example 2.

[0027] Figure 3 This is an SEM image of the fuel electrode support layer of a solid oxide fuel cell supported by two 100*100*0.40 mm industrial-grade fuel electrodes provided in Example 1.

[0028] Figure 4 This is a SEM image of the NiO slurry layer printed on the fuel electrode surface of a solid oxide fuel cell supported by two 100*100*0.40 mm industrial-grade fuel electrodes provided in Example 1. DETAILED DESCRIPTION

[0029] Example 1

[0030] Embodiment 1 of the present invention provides a method for solving nickel loss during sintering of a solid oxide fuel cell, comprising the following steps:

[0031] (1) Preparing NiO slurry;

[0032] (2) Preparation of solid oxide fuel cells supported by two 100*100*0.40 mm industrial-grade fuel electrodes (the preparation process refers to the embodiment described in CN118213585A), in which NiO slurry is printed on the surface of the fuel electrode before the co-sintering step of the fuel electrode and the electrolyte layer of one of the cells, and the fuel electrode and the electrolyte layer are co-sintered after drying, and both cells are placed on a zirconia support plate with the fuel electrode facing downward for high-temperature sintering.

[0033] The thickness of the NiO slurry printed on the fuel electrode surface is 3 μm.

[0034] The printing method is screen printing.

[0035] Calculated by mass percentage, the raw materials for preparing the NiO slurry include at least 70% NiO powder, 4% dispersant, and the balance is made up of organic carrier.

[0036] The D of the NiO powder 50 The particle size is 1μm.

[0037] The organic carrier is a combination of terpineol, 3-hydroxy-2,2,4-trimethylpentyl isobutyrate and ethyl cellulose, and the mass ratio of the terpineol, 3-hydroxy-2,2,4-trimethylpentyl isobutyrate and ethyl cellulose is 7.8:1.8:0.4.

[0038] The preparation method of the organic carrier is as follows: ethyl cellulose is mixed with pinene alcohol and 3-hydroxy-2,2,4-trimethylpentyl isobutyrate, and the mixture is placed at 120° C. for 4 hours to obtain the organic carrier.

[0039] The preparation method of the NiO slurry is as follows: NiO powder, a dispersant and an organic carrier are stirred and mixed, and then rolled to obtain the NiO slurry with a slurry fineness of less than 3 μm.

[0040] The dispersant is a phosphate ester.

[0041] Example 2

[0042] Embodiment 2 of the present invention provides a method for solving nickel loss during sintering of a solid oxide fuel cell, comprising the following steps:

[0043] (1) Preparing NiO slurry;

[0044] (2) Preparation of two 100*100*0.25 mm industrial-grade electrolyte-supported solid oxide fuel cells (the preparation process refers to the embodiment described in CN117457952A, wherein the amounts of raw materials and the parameters in steps 1.1 and 1.2 take intermediate values), wherein NiO slurry is printed on the surface of the fuel electrode of one of the cells before the fuel electrode sintering step, and the slurry is dried and co-sintered with the fuel electrode, and both cells are placed on an alumina support plate with the fuel electrode facing downward for high-temperature sintering.

[0045] The thickness of the NiO slurry printed on the fuel electrode surface is 3 μm.

[0046] The printing method is screen printing.

[0047] Calculated by mass percentage, the raw materials for preparing the NiO slurry include at least 70% NiO powder, 4% dispersant, and the balance is made up of organic carrier.

[0048] The D of the NiO powder 50 The particle size is 1μm.

[0049] The organic carrier is a combination of terpineol, 3-hydroxy-2,2,4-trimethylpentyl isobutyrate and ethyl cellulose, and the mass ratio of the terpineol, 3-hydroxy-2,2,4-trimethylpentyl isobutyrate and ethyl cellulose is 7.8:1.8:0.4.

[0050] The preparation method of the organic carrier is as follows: ethyl cellulose is mixed with pinene alcohol and 3-hydroxy-2,2,4-trimethylpentyl isobutyrate, and the mixture is placed at 120° C. for 12 hours to obtain the organic carrier.

[0051] The preparation method of the NiO slurry is as follows: NiO powder, a dispersant and an organic carrier are stirred and mixed, and then rolled to obtain the NiO slurry with a slurry fineness of less than 3 μm.

[0052] The dispersant is a phosphate ester.

[0053] Comparative Example 1

[0054] Comparative Example 1 of the present invention provides two 100*100*0.40mm industrial-grade fuel electrode-supported solid oxide fuel cells, and its specific implementation method is the same as that of Example 1, except that neither of the two batteries adopts the method provided in Example 1 for solving the problem of nickel loss during the sintering of solid oxide fuel cells.

[0055] Comparative Example 2

[0056] Comparative Example 2 of the present invention provides two 100*100*0.25mm industrial-grade electrolyte-supported solid oxide fuel cells, and its specific implementation is the same as Example 1, except that neither of the two batteries adopts the method provided in Example 2 for solving the problem of nickel loss during the sintering of solid oxide fuel cells.

[0057] Performance Testing

[0058] 1. A discharge test was performed on two 100*100*0.40 mm industrial-grade fuel electrode-supported solid oxide fuel cells provided in Example 1 and Comparative Example 1. The test conditions were: 750°C, hydrogen flow rate: 1 SLM, air flow rate: 3 SLM; the test results are shown in Figure 1 The discharge performance of the two batteries provided in Example 1 is 30% higher than that in Comparative Example 1.

[0059] 2. The two 100*100*0.25mm industrial-grade electrolyte-supported solid oxide fuel cells provided in Example 2 and Comparative Example 2 were tested for hydrogen production by electrolysis of water. The test conditions were: 750°C, hydrogen flow rate: water vapor flow rate = 1:9, hydrogen flow rate was 0.5SLM, and the electrolyte material was 8YSZ; the water electrolysis hydrogen production performance of the two batteries provided in Example 2 was 17% higher than that of Comparative Example 2.

[0060] 3. The fuel electrode support layer of the solid oxide fuel cell supported by two 100*100*0.40 mm industrial-grade fuel electrodes provided in Example 1 and the NiO slurry layer printed on the surface of the fuel electrode were characterized by SEM. Figure 3 , Figure 4 .

Claims

1. A method for solving nickel loss during sintering of solid oxide fuel cells, characterized in that: (1) Preparing NiO slurry; (2) For solid oxide fuel cells supported by the fuel electrode, NiO slurry is printed on the surface of the fuel electrode before the co-sintering step of the fuel electrode and the electrolyte layer, and the fuel electrode and the electrolyte layer are co-sintered after drying; For solid oxide fuel cells supported by the electrolyte, NiO slurry is printed on the surface of the fuel electrode before the sintering step of the fuel electrode, and the co-sintering with the fuel electrode is carried out after drying.

2. The method for solving nickel loss during sintering of solid oxide fuel cells according to claim 1, characterized in that: The thickness of the NiO slurry printed on the fuel electrode surface is less than 5 μm.

3. The method for solving nickel loss during sintering of solid oxide fuel cells according to claim 2, characterized in that: Calculated by mass percentage, the raw materials for preparing the NiO slurry include at least 30-90% NiO powder, 1-6% dispersant, and the balance is made up of organic carrier.

4. The method for solving nickel loss during sintering of solid oxide fuel cells according to claim 3, characterized in that: The D of the NiO powder 50 Particle size range: 0.5-3μm.

5. The method for solving nickel loss during sintering of solid oxide fuel cells according to claim 4, characterized in that: The organic carrier at least includes terpineol and ethyl cellulose.

6. The method for solving nickel loss during sintering of solid oxide fuel cells according to claim 5, characterized in that: The organic carrier also includes 3-hydroxy-2,2,4-trimethylpentyl isobutyrate.

7. The method for solving nickel loss during sintering of solid oxide fuel cells according to claim 6, characterized in that: The mass ratio of terpineol, 3-hydroxy-2,2,4-trimethylpentyl isobutyrate and ethyl cellulose is (5-9): (1-3): (0.1-1).

8. The method for solving nickel loss during sintering of solid oxide fuel cells according to claim 7, characterized in that: The preparation method of the organic carrier is as follows: ethyl cellulose is mixed with pinene alcohol and 3-hydroxy-2,2,4-trimethylpentyl isobutyrate, and then placed at 100-120° C. for 4-5 hours to obtain the organic carrier.

9. The method for solving nickel loss during sintering of solid oxide fuel cells according to claim 8, characterized in that: The preparation method of the NiO slurry is as follows: NiO powder, a dispersant and an organic carrier are stirred and mixed, and then rolled to obtain the NiO slurry with a slurry fineness of less than 3 μm.

10. The method for solving nickel loss during sintering of solid oxide fuel cells according to claim 9, characterized in that: The dispersant includes at least a phosphoric acid ester.

Citation Information

Patent Citations

  • Anode support type SOFC half-cell sintering method

    CN114335640A

  • Preparation method of solid oxide fuel cell

    CN117457952A

  • Preparation method of flat-plate anode-supported solid oxide fuel cell and solid oxide fuel cell

    CN118213585A